Marriage and Marriage Markets - Shoshana Grossbard (Institute for the Study of Labor (IZA), 2016)
This paper reviews models of marriage, with special emphasis on how the sex ratio (the ratio of marriageable men to women) can help explain measurable outcomes such as marriage formation, intra-marriage distribution of consumption goods, savings, labor supply, leisure, type of relationship, divorce, and intermarriage. Predictions are based on Demand and Supply analyses by Becker and the author. Evidence in support of the predictions is reported, most of it based on recent literature.
Keywords: E2; J11; J12; J16; J22; O15; R2; 330; marriage; marriage markets; sex ratio; savings; consumption; labor supply; cohort